Citrate-capped quantum dots of CdSe for the selective photometric detection of silver ions in aqueous solutions - Ingole, Pravin P.; Rajiv M. Abhyankar; Bhagavatula L. V. Prasad; Haram, Santosh K. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2010)
A simple strategy for the synthesis of water soluble, luminescent, citrate-capped CdSe quantum dots (Q-CdSe) and their applications to selective detection of silver ions are described. The steady state photoluminescence (PL) spectra show single, narrow emission band at ca. 554 nm without any contribution from the trap states. The effect of various ions including physiologically important metal ions (viz. K(+), Ca(2+), Fe(3+), Zn(2+), Mg(2+), Mn(2+), Cu(2+), Ag(+), Pb(2+) and Cd(2+)), on the PL intensity of citrate-capped Q-CdSe has been studied. Among these, selective luminescence quenching with Ag(+) ion was found to be predominant. Under the optimum conditions, the response was linear between 1.7 and 18 mu M. The quenching constant K(SV) was found to be ca. 3.4 x 10(5) M(-1). The mechanism of photoluminescence quenching of Q-CdSe by metal ions (Ag(+)) is also discussed. Based on these studies, the potential use of Q-CdSe as a luminescent probe for the selective detection of silver ion has been proposed. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Ag(+) ions; Luminescence quenching; Luminescent probe; Q-CdSe; Tri-sodium citrate

Basic structural motif and major biophysical properties of Amyloid-beta are encoded in the fragment 18-35 - Chandrakesan, Muralidharan; Sarkar, Bidyut; Mithu, Venus Singh; Rajiv M. Abhyankar; Bhowmik, Debanjan; Nag, Suman; Sahoo, Bankanidhi; Shah, Riddhi; Gurav, Sushma; Banerjee, Raja; Dandekar, Sucheta; Jose, Jaya C.; et al. (Chemical Physics, 2013)
Aggregation and misfolding of the amyloid beta (A beta) peptide is thought to initiate Alzheimer's disease (AD). Here we study the role played by its central segment (A beta(18-35)) in determining these properties. A beta(18-35) has a solubility of 18 mu M. The soluble fraction consists mainly of small oligomers, which have mixed beta-sheet and random coil structures. The monomer is mostly a random coil with some residual compactness. Aggregated A beta(18-35) forms fibrils of width 3.0 +/- 0.7 nm, which is consistent with a hairpin shape. Each of these properties has a close similarity to A beta(40). Remarkably, solid state NMR indicates that the fibrils also retain the secondary structure and tertiary contacts of A beta(40). This is the shortest fragment of A beta reported so far which preserves its fibrillar architecture, including the hairpin turn, as well as its solution phase conformational properties. Residues 18-35 should therefore be a key target of AD therapeutics. (C) 2013 Published by Elsevier B. V.
Keywords: Alzheimer's disease; Fluorescence correlation spectroscopy; Protein aggregation; Solid-state NMR